A inserção da educação ambiental no ensino superior : uma reflexão com coordenadores de ensino da Universidade Federal de Mato Grosso Câmpus de Rondonópolis - Araújo, Rosa Beatriz de (2019)
This dissertation results from a research enrolled in the Graduate Program in Education that aims to understand how the education coordinators of undergraduate courses have understood Environmental Education, regulated by Law 9.795 / 99, according to their expectations regarding the insertion of what establishes this item of said Law in the Pedagogical Projects of Course. Environmental Education is a primordial education, which makes citizens aware of the importance of sustainability in their daily life and in their professional and socio-environmental relations. In this way, higher education institutions should prepare future professionals for professional life as well as for living in society, arousing social and environmental awareness, investing in environmental education actions. We take as theoretical references the environmental education laws, and especially Law No. 9.795 / 99, which establishes the National Environmental Education Policy. This research will contribute to the contemporary debate on Socio-environmental Responsibility, especially in the field of higher education and the conscious formation of future professionals, since themes related to Environmental Education are still of little repercussion in the area of education in all modalities and all academic levels. The Communicative Investigation Methodology presupposes reality as a process, based on something that is being constructed and interpreted collectively, is based on the Habermas Theory of Communicative Action, as well as the concept of Freire's Dialogicity. We chose to use two techniques: communicative indepth interview and communicative discussion group. There were three phases in this methodological process, the first two being individual and the last in a group. The construction of the understanding about Environmental Education occurred throughout the research process, the group came to a common thought, how important is the insertion of Environmental Education in higher education and much to think and do about the subject in the university.